2009
DOI: 10.1016/j.pain.2009.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Placebo analgesia induced by social observational learning

Abstract: Although it has long been known that psychosocial factors play a crucial role in placebo responses, no attempt has been made to understand if social observation shapes the placebo analgesic effect. To address this question, we compared placebo analgesia induced through social observation (Group 1) with first-hand experience via a typical conditioning procedure (Group 2) and verbal suggestion alone (Group 3). In Group 1, subjects underwent painful stimuli and placebo treatment after they had observed a demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
337
6
28

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(392 citation statements)
references
References 36 publications
21
337
6
28
Order By: Relevance
“…In our data, this was reflected by positive correlations between agreeableness and m-opioid system activation in several midline regions (subgenual ACC, dorsal ACC and OFC) as well as the anterior and posterior insular cortex, NAc, amygdala and PAG. In this respect, agreeableness has also been linked to greater effectiveness of placebo acupuncture (Kelley et al, 2009) and empathic traits to placebo analgesia mediated through social learning (Colloca and Benedetti, 2009). Moreover, reciprocal altruism has been related to resilience (Charney, 2004) and the activation of brain areas linked to reward processing (Rilling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In our data, this was reflected by positive correlations between agreeableness and m-opioid system activation in several midline regions (subgenual ACC, dorsal ACC and OFC) as well as the anterior and posterior insular cortex, NAc, amygdala and PAG. In this respect, agreeableness has also been linked to greater effectiveness of placebo acupuncture (Kelley et al, 2009) and empathic traits to placebo analgesia mediated through social learning (Colloca and Benedetti, 2009). Moreover, reciprocal altruism has been related to resilience (Charney, 2004) and the activation of brain areas linked to reward processing (Rilling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these inconsistencies, it has been shown that placebo responsiveness, proneness to suggestionbased memory distortions, and hypnotic suggestibility are all associated with empathy (Colloca & Benedetti, 2009;Swider & Babel, 2013;Tomes & Katz, 1997;Wickramasekera & Szlyk, 2003), thereby implying that suggestibility may be related to the broader tendency to be influenced by social contextual cues. In a more extreme form, social cues can function as suggestions that elicit illness, as is the case with mass psychogenic illness (Jones et al, 2000;Mink, 2013).…”
Section: Hypnotic Suggestion In a Broader Contextmentioning
confidence: 99%
“…The various possible mechanisms that underlie NP include Pavlovian conditioning, expectations and previous social experiences. In fact both placebo and nocebo responses can be acquired through all kinds of learning and when these happen in the context of everyday clinical practice, these may emanate from either the patient's expectations or their previous similar experiences (4)(5)(6)(7)(8). Neurobiologically, dopamine and endogenous opiates have been shown to serve as the central mediators of these phenomena.…”
Section: Introductionmentioning
confidence: 99%